Acute histopathological responses of testicular tissues after different fractionated abdominal irradiation in rats. Issue 1 (January 2015) - Akdere, Hakan; Yurut Caloglu, Vuslat; Tastekin, Ebru; Caloglu, Murat; Turkkan, Gorkem; Mericliler, Meric; Mehmet Burgazli, Kamil
Abstract: Purpose : To compare the effects of different fractionated doses of abdominal radiation therapy on acute histopathological responses of testicular tissues in rats. Methods : Thirty-three 3-week-old Wistar albino rats were randomized into 6 groups: group 1 ( n = 5), control; group 2 (n = 4), hypofractionated total abdominal irradiation (TAI) of 6 Gy/1 fraction/day for 2 days; group 3 ( n = 6), hypofractionated TAI of 4 Gy/1 fraction/day for 3 days; group 4 ( n = 6), hypofractionated TAI of 3 Gy/1 fraction/day for 4 days; group 5 ( n = 6), conventionally fractionated TAI of 2 Gy/1 fraction/day for 6 days; group 6 ( n = 6), conventionally fractionated TAI of 1.7 Gy/1 fraction/day for 7 days. Mean epithelial length and diameter of seminiferous tubules of testicular tissues were determined after euthanasia. Results : Initially, a highly significant decrease in both the mean tubular diameter and epithelial height of the seminiferous tubules was demonstrated in all irradiated rats compared with the control group. No significant differences regarding both damage parameters were found between different hypofractionated radiation therapies. Both conventional radiation therapies reduced the epithelial height and mean diameter of the seminiferous tubules to a lesser extent when compared with 6 Gy/1 fraction/day hypofractionated therapy. It was further shown that parameter values were comparable between rats that received 3 Gy/day hypofractionated therapy and rats that received either of the two conventional therapies. Furthermore, although 4 Gy/day hypofractionation decreased tubular diameter and epithelial length to a greater degree compared with the conventional therapy of 1.7 Gy/1 fraction/day, no statistically significant difference was found when compared with conventional therapy of 2 Gy/1 fraction/day. Additionally, no statistically significant difference was demonstrated between the two types of conventional radiotherapy application. Conclusion : The present study demonstrated that hypofractionated abdominal irradiation leads to more prominent tissue damage in the testes than conventional irradiation.